Evaluation of antimicrobial action of Carie Care™ and Papacarie Duo™ on Aggregatibacter actinomycetemcomitans a major periodontal pathogen using polymerase chain reaction - Anil Kush; Rachna Thakur; Sandya Devi S Patil; Santhosh T Paul; Madhu Kakanur (Wolters Kluwer Medknow Publications, 2015)
Background: In the present scenario, we are made available with chemomechanical caries removal system containing a natural proteolytic enzyme for the ease in the excavation of infected dentine. The additive action for these agents is providing antimicrobial and anti-inflammatory properties. Aim: This study was undertaken for assessing the action of Carie Care™ and Papacarie Duo™ on Aggregatibacter actinomycetemcomitans. Materials and Methods: The samples were collected for cultivation of the periodontal pathogen from the clinical periodontal pockets using sterile paper points. The samples cultured under suitable conditions were analyzed with quantitative polymerase chain reaction targeting 16s r-DNA. The samples were divided into three groups namely, Group A: Control, Group B: With Papacarie Duo, Group C: With Carie Care. The pathogen inoculums plugs were inserted in the petri dishes containing chemically defined medium and the experimental gels at different concentrations and were incubated under optimal conditions. The inhibition of growth of the pathogen was studied visually. Results: There was visual inhibition of growth for Group B and C and also exhibited a dose-dependent effect also. Conclusion: Based on the results of the present study, Carie Care™ gel demonstrated better antimicrobial action against A. actinomycetemcomitans which is a major periodontal disease causing pathogen.